Anti-Müllerian hormone as a biomarker of ovarian function and spontaneous puberty in Turner syndrome: a systematic review - Bin-Abbas, Bassam; Jabari, Mosleh (Frontiers in Endocrinology, 2025)
BackgroundTurner syndrome (TS), caused by complete or partial X chromosome monosomy, often leads to primary ovarian insufficiency (POI) and pubertal delay. Anti-Müllerian hormone (AMH) is a key biomarker of ovarian reserve, but its predictive role in spontaneous puberty and ovarian function in TS remains unclear.MethodsThis systematic review followed PRISMA guidelines and included studies from PubMed, Embase, and Cochrane (2000–2025). Nine studies (865 TS patients, 976 controls) were analyzed. Outcomes included AMH levels in TS versus controls, association with spontaneous puberty, and predictive value for fertility preservation. Risk of bias was assessed using the Newcastle-Ottawa Scale.ResultsTS patients had significantly lower AMH levels than controls (weighted mean differences (WMD): -3.04 ng/mL, 95% CI: -3.26 to -2.83, p < 0.001). Detectable AMH correlated with spontaneous puberty (OR=5.12, 95% CI: 2.87–9.12), particularly in mosaic karyotypes. Subgroup analyses revealed assay variability, with ELISA-based methods detecting low but clinically relevant AMH levels. Sensitivity analyses confirmed robustness, and publication bias was minimal (Egger’s p = 0.283).ConclusionAMH is a reliable biomarker for ovarian reserve and spontaneous puberty prediction in TS. Its integration into clinical practice may improve fertility counseling and hormone therapy timing. However, standardized assays and prospective studies are needed to optimize its diagnostic accuracy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/ PROSPERO, identifier CRD420251051633.